GENERATION AND PERFORMANCE ANALYSIS OF GPS AND GLONASS VIRTUAL DATA FOR POSITIONING UNDER DIFFERENT IONOSPHERIC CONDITIONS - Jerez, Gabriel Oliveira; Alves, Daniele Barroca Marra (Boletim de Ciências Geodésicas, 2019)
Several approaches concerning the use in positioning of GNSS (Global Navigation Satellite Systems) can be considered: systems, applied methods and errors that can affect the signals. Following the GLONASS (GLObal NAvigation Satellite System) constellation reestablishment (2011), there was renewed interest in its use with GPS (Global Positioning System). Different possibilities are available concerning applied methods, such as the virtual reference station (VRS) concept (it is possible to obtain data for a virtual station that does not physically exist, using data from a network). One of the main sources of error related to the GNSS signal, is the ionosphere. Many studies have been developed aiming to evaluate GPS positioning quality and influences that can affect it, but there are still several investigation possibilities concerning GLONASS. In this context, this research is intended to assess the GPS/GLONASS virtual data positioning performance considering regions and periods with different ionospheric behavior. A high correlation between the results from virtual and real data (Pearson’s correlation coefficients around 0.8) was noticed. GPS/GLONASS data performance presented better mean squared error results compared to GPS alone (average 3D improvement was 45 cm - 49%). In addition, it was possible to verify ionosphere influence in the positioning error, taking into account station region and period of the year.